Environmental Homeopathy: Homeopathic Potencies Regulate the Growth and Toxicity of Raphidiopsis raciborskii (Cyanobacteria) and can be Tracked Physico-Chemically. Part 2: Physico-chemical Results - Mohammad, Suham Nowrooz; Pinto, Andreia Adelaide G.; Silva, Rodrigo Augusto da; Suffredini, Ivana Barbosa; Tournier, Alexander L.; Cartwright, Steven J.; Yunes, João Sarkis; Bonamin, Leoni V. (Homeopathy, 2024)
Introduction The control of cyanobacterial toxicity and growth by homeopathic potencies was described in Part 1 of this two-part report. Here, a parallel approach characterized the physico-chemical features of the potencies used and the liquid media treated with them, correlating these results with their respective biological effects.Objectives Our objective was to establish if physico-chemical parameters can track homeopathic potencies in seawater or artificial seawater medium (ASM)-1 and to discover whether these parameters correlate with previously described biological effects.Method Artemia franciscana (brine shrimp) cysts were cultivated in seawater challenged with Raphidiopsis raciborskii extract and treated with different homeopathic potencies chosen from a screening process. Cultures of R. raciborskii maintained in ASM-1 were also treated with previously screened homeopathic potencies, and their growth was monitored as a function of time. The physico-chemical properties of the treated media (seawater or ASM-1) were evaluated by their interaction with solvatochromic dyes and changes in pH, conductivity and temperature.Results Coumarin 7 was found to be a marker for Nitric acidum 6cH and Isotherapic (R. raciborskii extract) 200cH in seawater (analysis of variance [ANOVA], p = 0.0015). Nile red was found to be a marker for Nitric acidum 200cH and Mercurius solubilis 30cH in ASM-1 (ANOVA, p ≤ 0.001). An increase in pH of ASM-1 and endothermic effects were observed after these treatments (two-way ANOVA, p = 0.0001). Seawater and ASM-1 to which potencies had been added were also subjected to a constant unidirectional 2,400 Gauss static magnetic field and found to have enhanced effects on the solvatochromic dyes tested.Conclusion Homeopathic potencies were specifically traceable in aqueous media using solvatochromic dyes, especially when the samples were subjected to a magnetic field. Results from monitoring other physical parameters, such as pH and temperature, were less specific in relation to potency tracking. However, potency-induced endothermic effects might provide valuable thermodynamic data relating to the nature of potencies.
Keywords: water; solvatochromic dyes; physico-chemical markers; homeopathy